Could the Golden Mean Theory Lead Us to a Good Life? - Manesi, Stavroula (Conatus - Journal of Philosophy, 2018)
Aristotle’s views on the golden mean have been heavily criticized. For example, it is often claimed that the golden mean is not the same for all people, or that there are cases where this golden mean simply does not exist. Indeed, these objections seem to be justifiable and grounded. Against these views I will claim that any prudent person that adheres to reason is capable of finding Aristotle’s golden mean, even if it is not obvious from the beginning. In that sense, I will conclude, Aristotle provides a good answer to Socrates’ question, "how should people live?"